ANALISIS PERUBAHAN TINGKAT KONSEPSI SAINS FISIKA SISWA MENGGUNAKAN MODEL PEMBELAJARAN POE (PREDICT-OBSERVE-EXPLAIN) PADA MATERI MOMENTUM DAN IMPULS KELAS X MAN 1 PEKANBARU - Hopsah Nurpatmawati; Nur Islami; Fakhruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The propose of this study is to determine the level of students' conceptions change in momentum and impulse materials using POE learning model (predict-observe-explain) in class X MAN 1 Pekanbaru. The research was conducted from March to July 2017. The population of this research is all student of class X MAN 1 Pekanbaru. The sampling method used simple random sampling with a total sample of 48 students, the class X MIA 1 as an experimental class consists of 24 students and class X MIA 4 as the control class Totaling 24 students. Type of research is quasi experiment design with nonequivalent control group design. The data collection instrument used in this research is the initial and final diagnostic test consisting of 10 objective questions. Based on the data analysis in the control class the percentage of students who have the correct conception (level 2) before the learning is 29.85% and after learning with conventional learning obtained the percentage of students who have the correct conception is 54.16%. In the experimental class the percentage of students who have the correct conception (level 2) before the learning is 29.62% and after the learning by using the model of learning POE obtained percentage of students who have the correct conception is 57.17%. The increase of the percentage of students who have the correct conception on the control class is 24.31% and in the experimental class is 27.55%. So it can be concluded that the model of learning POE can improve student conception on the material momentum and impulse in class X MAN 1 Pekanbaru.Keywords: Conception Rate Changes, Momentum And Impulse, Poe (Predict-Observe- Explain)